Easy Knitted Scarves - Russel, Monica (Twenty to Make, 2013)
Twenty beautiful scarf patterns for you to knit, accompanied by information on the wools and needles needed and inspirational photographs. Knit the perfect gift for a loved one, or simply give them the book to try themselves.